Critical Analysis of Neo-Gramscian Hegemony - Cader, Indira Thalia; Sundrijo, Dwi Ardhanariswari (Green Publisher Indonesia, 2023)
This paper aims to present a critical analysis of Neo-Gramscianism, a theoretical framework rooted in the works of Antonio Gramsci, especially regarding its understanding of hegemony. This paper use critical theory by Frankfurt School as a foundation in criticizing the concept of hegemony argued by Robert Cox. While Neo-Gramscianism offers valuable insights, this study seeks to unveil its inherent limitations. Departing from the question of, “Do the concepts provided by Neo-Gramscian about Hegemony solve the problem of marginalized communities?” and using Frankfurt School’s critical theory as the analytical framework, the analysis highlights several key flaws. Firstly, the epistemological failure it reflects, the overemphasis on two-way hegemony or by consent has overlooked a significant factor, which is the inevitable resistance of subaltern class. This movement would presumably trigger the elite class to force their power onto the subaltern class, which would engage the two classes in a series of material and ideological struggles, and eventually will result in the persistence of domination. Secondly, this critical analysis also assesses the internal fallacies of Neo-Gramscian with Horkheimer’s criteria on Critical Theory. This paper concludes that the promised two-way hegemony initiated by Robert Cox fails to solve the problem of marginalized communities, since it is inherently not a Critical Theory, by its utilization of power relations, top-down approach, and most importantly, centralization of power.